Role of Cardiovascular Imaging in the Follow-Up of Patients with Fontan Circulation - Sara Moscatelli; Nunzia Borrelli; Jolanda Sabatino; Isabella Leo; Martina Avesani; Claudia Montanaro; Giovanni Di Salvo (MDPI AG, 2022)
Since its first description in 1971, the Fontan procedure and its modifications have led to a substantial improvement in the survival rates of patients with a variety of types of complex Congenital Heart Disease (CHD) characterised by the presence of a single, dominant ventricle. However, despite the significant improvement of the prognosis over the years, Fontan patients are still exposed to several cardiovascular and systemic complications. It is, therefore, important to fully understand the pitfalls hidden behind a Fontan anatomy and the potential predictors of ventricular failure. Cardiovascular imaging plays a key role in this context, allowing for the early identification of complications with important prognostic implications. Echocardiography remains the first-line imaging modality for serial evaluation of Fontan patients. However, there is a growing role of cardiovascular magnetic resonance and cardiac computed tomography from pre-operative assessment to longitudinal follow-up. The aim of this paper will be to provide a comprehensive overview of the role, strengths, and weaknesses of each imaging modality in the assessment of congenital cardiac conditions palliated with the Fontan procedure.